Common factors blamed for high prevalence of smoking among rural adult population in Malaysia - Juni, Muhamad Hanafiah; Muhamad Saliluddin, Suhainizam; Mohd Shuhaimi, Fatin Adlena; Roslan, Nur Atiqah; Karuthan, M. (BEST Journals, 2014)
Background: The tobacco smoking epidemic has become an immense public health threat especially in developing countries. Tobacco smoking is risk factor toward many non-communicable diseases such as cardio-vascular diseases, cancer, respiratory diseases, peptic ulcers and other smoking-related conditions. Prevalence of tobacco smoking in rural areas in Malaysia has shown an increasing trend and had shown higher prevalence compared to general population and population in urban area. Objective: The objectives of the study is to determine the prevalence and common factors associated with smoking among rural adult population in Malaysia. Methodology: A cross-sectional study was carried out among 510 adults who are residing in a rural area in Malaysia. The respondents were selected randomly among rural population residing in a rural area in Negeri Sembilan, Malaysia. Face to face interviews were carried out validated questionnaire developed for this study. Results: The response rate was 96.7%. Prevalence of non-smokers, those who ever smoked and current smokers were 57.3% (95% CI 53, 61.8), 8.5% (95% CI 6.6, 11.7) and 34.2% (95% CI 29.6, 38) respectively. Among this rural population smoking is significantly associated with gender (p=0.000), occupation (p=0.000), level of education (p=0.008), peer influence (p=0.000), family influence (p=0.000), level of stress (p=0.001) and level of knowledge (p=0.029). Age (p=0.215) and family income (p=0.464) were not significantly associated with smoking. Conclusions: This study reveals a high prevalence of smoking among rural adults in Malaysia. Common factors associated with smoking among rural population in this study are common among men, occupational status, level of education, peer and family influence, stress and level of knowledge.